The Association between High Body Mass Index and Mortality Risk in Hospitalized Patients Diagnosed with COVID-19: A Meta-Analysis - Yuzana Maung; Eti Poncorini Pamungkasari; Bhisma Murti (Masters Program in Public Health, 2021)
Background: COVID-19, caused by severe acute respiratory coronavirus 2 (SARS-CoV-2), emerged as a global pandemic with confirmed death cases of more than 1.27 million worldwide. Since the past pandemic, several studies discovered the adverse effects of excess fat accumulation on the severity of viral infections. This study aimed to investigate the association between high body mass index (BMI) and mortality risk in hospitalized COVID-19 patients based on four categories of high BMI ranges. Subjects and Method: A systematic review and Meta-Analysis was conducted using search articles from electronic databases including PubMed, Google Scholar, and Scopus, published from 2019 to 2021. The keywords used to retrieve articles were